If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 3(4x + -1) = 6(2x + -5) + 29 Reorder the terms: 2 + 3(-1 + 4x) = 6(2x + -5) + 29 2 + (-1 * 3 + 4x * 3) = 6(2x + -5) + 29 2 + (-3 + 12x) = 6(2x + -5) + 29 Combine like terms: 2 + -3 = -1 -1 + 12x = 6(2x + -5) + 29 Reorder the terms: -1 + 12x = 6(-5 + 2x) + 29 -1 + 12x = (-5 * 6 + 2x * 6) + 29 -1 + 12x = (-30 + 12x) + 29 Reorder the terms: -1 + 12x = -30 + 29 + 12x Combine like terms: -30 + 29 = -1 -1 + 12x = -1 + 12x Add '1' to each side of the equation. -1 + 1 + 12x = -1 + 1 + 12x Combine like terms: -1 + 1 = 0 0 + 12x = -1 + 1 + 12x 12x = -1 + 1 + 12x Combine like terms: -1 + 1 = 0 12x = 0 + 12x 12x = 12x Add '-12x' to each side of the equation. 12x + -12x = 12x + -12x Combine like terms: 12x + -12x = 0 0 = 12x + -12x Combine like terms: 12x + -12x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 52+3x=9x+16 | | 14ab+3d+5ab-2d= | | 45*0.3+30+x*0.4=60 | | 14r-3r+r= | | 30-4*(2+1)= | | 6ab-2ab-ab= | | 1.5/75= | | 7y+11=3y+25 | | (5-a)(2a+5)=0 | | x+.33=3x-.83 | | 62-5x=10+17 | | -3(5s-5)-15=-3(9s+0)-4 | | 6(n)+12=21 | | x+.66=3x | | 8y-6x=9y-1+5(3-6) | | 24x+34x=5 | | 91-5x=13x+23 | | -2(13+x)=5(-4x+2) | | -3-4=9-8x | | X=2x-x+x | | x=x-x+x | | 3x+5=2(x-6) | | x=-5+2.5y | | x^2+2x+2=0.97 | | 7y+5=-y-11 | | 4(5x-16)=20(x-4) | | 6+3r-3=8r+5-4r | | 4+3*4=28 | | 4x(2)-3x-5=0 | | 5x(2)-10x-6= | | 4x(2)-1=-5x | | 2(x)2+15x=17 |